Advanced electrostatic plasma lenses on permanent magnets - Chekh, Yu.; Goncharov, A.; Protsenko, I. (Вопросы атомной науки и техники, 2006)
In the paper we summarize the recent results on the wide-aperture electrostatic plasma lenses using permanent magnets (in particular, the lenses with minimized magnetic field gradients). The lenses are investigated at the focusing of the pulsed medium-energy (~20 keV) high-current (up to 0,5 А) beams of heavy ions (Сu), generated by multi-aperture vacuum-arc ion source. The obtained static and dynamic characteristics of focused ion beams enable to determine the main factor, which determines the restriction of the maximum compression factor of the ion beams at low magnetic fields. In the range of strong magnetic fields we establish the possibility for large-scale electron vortices to be generated in a plasma lens.